Critical nitrogen dilution curve for processing potato in Argentinean Humid Pampas - Giletto, Claudia Marcela; Echeverria, Hernan Eduardo (Springer, 2019)
For processing potato, a new algorithm has been developed to determine nitrogen (N) requirement (NR) applying critical N dilution curve (Nc). The objectives of this work were i) to determine the Nc for processing potato under the growing conditions of the Argentinean Humid Pampas; ii) to compare the parameters of the Nc with those of the Nc obtained by other authors, and iii) to establish the crop NR. The experiments were carried out during four growing seasons. The cultivar Innovator was planted in a randomized complete block design with four N treatments. Dry matter yield and N concentration of shoots and tubers were measured during the growing season. The Nc was determined by selecting data points for which the highest total biomass (W), comprised of shoots and tubers, was obtained and by expressing N concentration as function of W. The N nutrition index (NNI) was determined as the ratio between the actual N concentration (Na) and the Nc. The NR was determined as the difference between actual N uptake and the critical N uptake, divided the N utilization efficiency. A fitted Nc (Nc = 5.30 W–0.42, R2 = 0.92) presented similar values than a published reference Nc. The relation between relative tuber yield (RY) and NNI was expressed by a linear-plateau function and accounted for 69% of the variation. For a NNI ≥ 1 the RY was near 98.7%. With decreasing NNI below 1 the RY decreased. The relation between RY and NR was expressed by a linear-plateau function and accounted for 66% of the variation. For a NR ≥ 0 the RY was near 98%. With decreasing NR, below 0, the RY decreased. Furthermore, the NNI increased linearly with increasing NR, which indicates that the NNI was 0.99 when NR was zero. This study has shown that Nc can be applied in potato crop systems. The NNI calculated from that curve is a reliable indicator of the N stress level during potato’s growing season. The critical N uptake and the actual N uptake enable the calculation of crop NR.